Corduroy [videorecording (DVD)] : and more stories about friendship - Freeman, Don, 1908-1978; Raschka, Christopher; Asch, Frank; Vagin, Vladimir Vasilʹevich, 1937-; Melmed, Laura Krauss; LaMarche, Jim (New Video, 2003)
Corduroy: Corduroy tries to find his lost button, so that someone will finally take him home from the department store. Yo! Yes?: Two boys become friends and they no longer have to play alone. Here comes the cat!: A village of mice is about to be visited by a cat.